Linking multiscale deformation to microstructure in cortical bone using in situ loading, digital image correlation and synchrotron X-ray scattering. (15th March 2018) - Gustafsson, Anna; Mathavan, Neashan; Turunen, Mikael J; Engqvist, Jonas; Khayyeri, Hanifeh; Hall, Stephen A; Isaksson, Hanna
Graphical abstract: Abstract: The incidence of fragility fractures is expected to increase in the near future due to an aging population. Therefore, improved tools for fracture prediction are required to treat and prevent these injuries efficiently. For such tools to succeed, a better understanding of the deformation mechanisms in bone over different length scales is needed. In this study, an experimental setup including mechanical tensile testing in combination with digital image correlation (DIC) and small/wide angle X-ray scattering (SAXS/WAXS) was used to study deformation at multiple length scales in bovine cortical bone. Furthermore, micro-CT imaging provided detailed information about tissue microstructure. The combination of these techniques enabled measurements of local deformations at the tissue- and nanoscales. The orientation of the microstructure relative to the tensile loading was found to influence the strain magnitude on all length scales. Strains in the collagen fibers were 2–3 times as high as the strains found in the mineral crystals for samples with microstructure oriented parallel to the loading. The local tissue strain at fracture was found to be around 0.5%, independent of tissue orientation. However, the maximum force and the irregularity of the crack path were higher when the load was applied parallel to the tissue orientation. This study clearly shows the potential of combining these different experimental techniques concurrently with mechanical testing to gain a better understanding of bone damage and fracture over multiple length scales in cortical bone. Statement of Significance: To understand the pathophysiology of bone, it is important to improve our knowledge about the deformation and fracture mechanisms in bone. In this study, we combine several recently available experimental techniques with mechanical loading to investigate the deformation mechanisms in compact bone tissue on several length scales simultaneously. The experimental setup included mechanical tensile testing in combination with digital image correlation, microCT imaging, and small/wide angle X-ray scattering. The combination of techniques enabled measurements of local deformations at the tissue- and nanoscales. The study clearly shows the potential of combining different experimental techniques concurrently with mechanical testing to gain a better understanding of structure-property-function relationships in bone tissue.